JUVENILE PREVENTION FOR INTERNALLY DISPLACED PERSONS: ORGANIZATIONAL AND TACTICAL PRINCIPLES (Bulletin of criminological association of Ukraine, 2024)
The article highlights the activities of juvenile prevention units in assisting internally displaced persons regardless of their age, gender or social status. Particular attention is paid to the relevance and necessity of providing psychological support not only to children, who are the most vulnerable category, but also to their parents. Ensuring a stable mental state of the whole family is seen as an important factor in the social stability of society in the context of modern challenges. It is noted that special emphasis should be placed on working with children, who, due to their age and vulnerability, are particularly affected by the consequences of displacement. The importance of organizing trainings and consultations for parents, as well as cooperation with specialists in the field of mental health and social support, is considered. The article emphasizes that providing comprehensive assistance to internally displaced persons contributes to strengthening social cohesion and restoring the vital potential of society as a whole.
Keywords: military aggression; psychological support; children; internally displaced persons